Immunoglobulin E and G Levels in Predicting Minimal Change Disease before Renal Biopsy. (11th November 2018) - Hsiao, Ching-Chung; Tu, Kun-Hua; Hsieh, Chun-Yih; Lee, Cheng-Chia; Chang, Chih-Hsiang; Fan, Pei-Chun; Tian, Ya-Chung; Fang, Ji-Tseng
Abstract : Purpose . The diagnosis of minimal change disease in adults relies mainly on renal biopsy, but this procedure is not without complications. Despite the advancements in technique of percutaneous renal biopsy, biopsy-related complications still occur. Bleeding is one of the major complications, which may lead to hemodynamic instability and, sometimes, even death. Thus, we developed a model to predict MCD for high-risk patients unsuitable for renal biopsy. Methods . We enrolled 142 patients with nephrotic syndrome who received renal biopsy between October 2007 and April 2011 at one tertiary medical center in this study. Demographic, clinical, and prebiopsy laboratory variables were retrospectively recorded and analyzed. Results . The overall prevalence of MCD was 26.8%. Age, hemoglobin levels, 24-hour urine protein, immunoglobulin (Ig) G, and IgE differed significantly between the MCD and non-MCD groups. Logistic regression analysis showed a significant increase in the risk of developing MCD as the number of Ig risk factors, namely, IgG < 450 mg/dl and IgE > 110 mg/dl, increased. Having both risk factors significantly increased the chances of receiving a diagnosis of MCD (by 31.84-fold, P =.007) compared with having neither. Combining the aforementioned clinical model and the 2 Ig risk factors was the best in predicting the diagnosis of MCD, with the area under a receiver-operating characteristic curve of 0.91. Conclusions . Combining clinical model and this 2 Ig risk factors provides physicians simple and valuable clinical markers to diagnose MCD.